Validity of the Deed of Relaas at the General Meeting of Shareholders (GMS) via Teleconference - Nurul Izzah; Maman Sudirman; Benny Djaja (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
The existence of GMS relaas activities via teleconference which previously only took the form of paper has become an electronic document, in its implementation it is difficult to confirm its validity, however, ratification in the form of a deed is one of the roles of a notary to create evidence in the form of an authentic deed of the General Meeting of Shareholders (GMS). The research method uses normative juridical analysis using legal data in an open source. Based on the research results, ratification of the GMS deed through teleconference media can be implemented because it is based on the law in Article 77 of Law Number 40 of 2007 concerning Limited Liability Companies, which must be followed by ratification from a notary, also supported in terms of implementation by the Services Authority Regulation Finance Number 16/POJK.04/2020. Apart from that, the validity of the notary's signature in the GMS deed allows participants in the GMS forum. The creation of a GMS relaas deed with electronic signing has also been regulated in the Information and Electronic Transactions Law. The contribution of this research material related GMS deeds of release in the company scope.